Are There Shortages and Regional Disparities in Lecanemab Treatment Facilities? A Cross-Sectional Study - Kazuki Ohashi; Ikuko Takahashi-Iwata; Zhao Jieyu; Ken Sakushima; Ichiro Yabe; Katsuhiko Ogasawara (SAGE Publishing, 2024)
Introduction: Alzheimer disease (AD) is the most common type of dementia, affecting 70% of patients with dementia. In Japan, over 5 million people aged 65 years and older had dementia in 2018, and this figure is expected to rise to 25% to 30% of this age group by 2045. In Japan, lecanemab, which was approved in 2023, is expected to be a new treatment for AD. However, lecanemab requires stringent management, including amyloid PET scans and MRI monitoring, necessitating specialized facilities, creating concerns regarding the lack of treatment facilities and poor treatment access. Methods: This study assessed spatial accessibility to lecanemab in Hokkaido, Japan, using geographic information system data. Hospitals were categorized into 3 scenarios based on their capacity to meet the treatment criteria. Service area analysis in each scenario evaluated the population coverage within 30-, 60-, and 120-minute travel times. The inverted two-step floating catchment area method was used to calculate the potential high-demand areas index (PHDI) for each hospital. Results: Population coverage ranged from 56% to 97%, depending on the scenario and travel time. Coverage for the most feasible scenario (Scenario 1) was 56%, 73.9%, and 88.3% within 30, 60, and 120 minutes, respectively. Northern and southern Hokkaido had the lowest coverage. PHDI analysis identified high-demand areas, with Sapporo facing potential overcapacity issues. Conclusion: Lecanemab highlights the need for strategic resource allocation to enhance accessibility and capacity. Establishing additional treatment centers, particularly in areas with poor accessibility and capacity, is crucial to maximize the benefits of treatment for dementia.